TO THE METHODOLOGY FOR EVALUATING THE REMODELING OF THE SAME ARTERIES OF AN ELASTIC-MUSCULAR TYPE - Задорожная, Марина Петровна; Разумов, Владимир Валентинович (Medicine in Kuzbass, 2019)
Classical methods for assessing the elastic properties of blood vessels dating back to the times of Jung, Moens, and Korteweg; a method for determining the propagation velocity of a pulse wave proposed by G.F. Langom at the beginning of the 20s of the last century, duplex scanning of peripheral arteries, as well as modern methods of contour analysis of pulse waves with the determination of the cardial-ankle vascular index and the brachial-ankle pulse wave velocity in relation to the study of vascular pools having paired arteries suffer from a lack of dualistic presentation of information about their condition separately for the left and right halves of the body. In the absence of a method for assessing the compliance of the arterial system as a whole, an integrated assessment of the state of vascular pools with paired arteries accessible to clinical study remains an urgent problem.The purpose of the study is to determine the relevance of bilateral asymmetric stiffness indicators of the same arteries of the carotid and phe-moral pools and to create a method for the integral assessment of their remodeling.Material and methods. Assessment of the morphological and functional parameters of the elastic properties of the arteries of the carotid and femoral pools in 110 patients with uncomplicated hypertension.Results. Not only bilateral asymmetry of remodeling within each vascular basin was revealed, but also interbasin, indicating heterotopic asynchronism of remodeling, excluding the possibility of using any of the arteries of the carotid and femoral pools as representative of the state of the vascular region. A technique is proposed for the integral assessment of the state of the carotid and femoral pools in the form of a single virtual artery for each of them without loss of information about the degree of remodeling expressed in them, and providing the possibility of a more meaningful comparison of it with variables with systemic modality than the technique of separately comparing them with stiffness parameters of left-right vessels.
Keywords: regional vascular basins; arterial stiff bone; asymmetry of the elastic parameters of arteries; arterial compliance